Health-disease and self-care practicing from the point of view of HIV/AIDS bearers - Caetano, Joselany Áfio; Pagliuca, Lorita Marlena Freitag; Maciel, Maria Fátima de Araújo (Rev Rene, 2003)
Descriptive study with qualitative approach that aimed at knowing health concept and identifying self-care deficit concerning people who have HIV/SIDA. It was developed in the National Network of People Living with HIV/SIDA – Ceara branch (RNP/CE), in the first two weeks of January 2002, starting from the realization of a workshop called Ocular Auto-Exam, during 30 hours, involving a population of 20 people who have HIV/SIDA. Empiric health categories associated to health conceptions is social, is vigor and production, is self-care, is God’s gift, limited to the immediate and to the individual, with no correlation with macro-structural determiners. Self-care deficit was: ingestion of liquid, feeding, insomnia, social interaction and difficulty of adhering to treatment. It is important the awareness of this reality lived by subjects in order to allow the development of actions and wider activities, searching for social transformations necessary to a better quality of life, both collective and individual, concerning SIDA.